Perbandingan efektivitas penggunaan database makanan berbasis website, dekstop dan buku pada mahasiswa gizi di Indonesia - Putri Dwi Kurnianingsih Darely; Muhammad Iqbal (AcTion: Aceh Nutrition Journal, 2019)
Until now, technology is growing where humans always update technological developments to get things easier and more efficient. One of them is in the database of food nutrient content, currently from the beginning covered in books and computers, experts develop an information media, such as in the form of online media in the form of websites. The purpose of this study is to compare the effectiveness of a website, desktop and book based food database. Research with analytic-comparative design with cross sectional approach was carried out on 415 active nutrition students throughout Indonesia taken using the snowball sampling method. The study was conducted in August-November 2018. Dependent variables are website, desktop, books and independent variables effective use of the food database. data were analyzed by Anova test and LSD Post-Hoc test. There was a significant difference in the effectiveness of database use of food nutrition (p= 0,001) with the average Website results (8,00 ± 1,09) higher than desktops (7,77 ± 1,26) and books (6.95 ± 1.64). The use of a Website-based food database is more effective than the desktop base and book base.